PRESENCE OF CAMPYLOBACTER SPP IN POULTRY MEAT AND CECUM IN LIMA, PERU - Lucas L., Juan (2013)
The aim of this study was to determine the presence of Campylobacter spp in meat and cecum of broilers sold in three illegal abattoirs in Lima, Peru. For this purpose, 90 broilers were selected, collecting 60 samples of body carcasses by the rinse method and 30 samples of cecum. The samples were cultured in mCCDA agar at 42 °C for 48 h under microaerophilic atmosphere, and biochemical tests were used to identify thermotolerant Campylobacter species. The results showed that 16.7% of carcasses were positive, where 60% were C. jejuni and 40% C. coli. In cecum samples, 26.7% were positive to Campylobacter spp, where 72.7% were C. jejuni and 27.2% C. coli.